Global Matrix 3.0 physical activity report card for children and youth: a comparison across Europe. (October 2020) - Coppinger, T.; Milton, K.; Murtagh, E.; Harrington, D.; Johansen, D.; Seghers, J.; Skovgaard, T.; Chalkley, A.; ,
Abstract: Objectives: The Global Matrix of report card grades on physical activity serves as a public health awareness tool by summarising the status of child and youth physical activity prevalence and action. The objectives were to: (1) provide a detailed examination of the evidence informing the 'School' and 'Community and Environment' indicators across all participating European Global Matrix 3.0 countries; (2) explore the comparability of the grades for these two indicators across Europe; (3) detail any limitations or issues with the methods used to assign grades; and (4) provide suggestions on how future grading of the indicators could be improved. Study design: A comparative review of published methods on the grading of Global Matrix 3.0 indicators across European countries. Methods: Key documents relating to the European countries involved in the 2018 Global Matrix 3.0 were collated and a template used to extract data for both the 'School' and 'Community and Environment' indicators. Results: Seventeen of the 20 European Report Card countries (85%) had a grade for schools, and 15 countries (75%) had a grade for community and environment. All countries considered between one and five factors when assigning the grade for these indicators. There were wide disparities in the number and sources of evidence used to assign the grades for both indicators, limiting the comparability of the evidence between different countries. Conclusion: To enable comparability, the authors recommend moving towards an agreed standardised set of metrics for grading each indicator. Furthermore, it would be useful to develop and share common tools, methods and instruments to collect data in a uniform way across countries, where possible. Such action will ultimately make the Global Matrix a more robust and useful tool for the future. Highlights: This study critiques the comparability of Global Matrix grades across Europe. There is a high degree of variability when assigning grades in the Global Matrix. An agreed standardised set of measures is needed to make the Global Matrix a more robust tool.